Rare but diverse off-target and somatic mutations found in field and greenhouse grown trees expressing CRISPR/Cas9 - Goralogia, Greg S.; Andreatta, Isabella M.; Conrad, Victoria; Xiong, Qin; Vining, Kelly J.; Strauss, Steven H. (Frontiers in Bioengineering and Biotechnology, 2024)
CRISPR gene editing, while highly efficient in creating desired mutations, also has the potential to cause off-target mutations. This risk is especially high in clonally propagated plants, where editing reagents may remain in the genome for long periods of time or in perpetuity. We studied a diverse population of Populus and Eucalyptus trees that had CRISPR/Cas9-containing transgenes that targeted one or two types of floral development genes, homologs of LEAFY and AGAMOUS. Using a targeted sequence approach, we studied approximately 20,000 genomic sites with degenerate sequence homology of up to five base pairs relative to guide RNA (gRNA) target sites. We analyzed those sites in 96 individual tree samples that represented 37 independent insertion events containing one or multiples of six unique gRNAs. We found low rates of off-target mutations, with rates of 1.2x10 -9 in poplar and 3.1x10 -10 eucalypts, respectively, comparable to that expected due to sexual reproduction. The rates of mutation were highly idiosyncratic among sites and not predicted by sequence similarity to the target sites; a subset of two gRNAs showed off-target editing of four unique genomic sites with up to five mismatches relative to the true target sites, reaching fixation in some events and clonal ramets. The location of off-target mutations relative to the PAM site were essentially identical to that seen with on-target CRISPR mutations. The low rates observed support many other studies in plants that suggest that the rates of off-target mutagenesis from CRISPR/Cas9 transgenes are negligible; our study extends this conclusion to trees and other long-lived plants where CRISPR/Cas9 transgenes are present in the genome for two or more years.